Bleb resuscitation of failing, leaking and dysfunctional blebs: A review - Arshi Singh; Kirti Singh; Aastha Singh (Indian Journal of Ophthalmology)
The success of trabeculectomy surgery depends on the longevity of the filtering bleb. Bleb failure can be categorized into two types: the scarred bleb with high intraocular pressure or the over-filtering and leaking bleb with low intraocular pressure. Bleb scarring is an insidious process over time as a consequence of excessive subconjunctival fibrosis. Timely recognition and early intervention utilizing a stepped-up approach are important for resuscitating the bleb and salvaging the trabeculectomy. Over-filtration and leaky bleb on the other end of the spectrum lead to failure of optimal bleb function and require a different management approach. This review discusses in detail various surgical techniques to revive dysfunctional blebs with a special focus on bleb needling. Timely identification and multifaceted management of bleb-related complications is the key to ultimately improving long-term success rates and patient outcomes.